2012
DOI: 10.4028/www.scientific.net/amr.548.617
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modelling and Optimization of Photochemical Machining

Abstract: Photochemical Machining is a novel machining process capable of processing wide range of hard-to-machine materials. This research addresses modelling and optimization of the process parameters for this machining technique. To model the process a set of experimental data has been used to evaluate the effects of various parameter settings in machining of SS316L. The process variables considered here include etchant temperature, time and concentration. Undercut, as one of the most important output characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 9 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…Unfortunately, in the real world, the etchant composition changes continuously. As an n-valent metal is dissolved into solution, etchant is consumed and the by-products of ferrous chloride (FeCl3) and metal chlorides are generated [5].…”
Section: Processmentioning
confidence: 99%
“…Unfortunately, in the real world, the etchant composition changes continuously. As an n-valent metal is dissolved into solution, etchant is consumed and the by-products of ferrous chloride (FeCl3) and metal chlorides are generated [5].…”
Section: Processmentioning
confidence: 99%
“…Chen et al [ 7 ] investigated the impact of hydrofluoric acid (HF) concentration in the etching solution on etching efficacy and found that the morphology of the channel could be altered by manipulating the proportion of HF present in the etching solution. Saraf et al [ 8 ] identified that the surface roughness after etching was greatly influenced by the etching duration and etching solution composition, rather than temperature, which had a negligible impact. Agrawal et al [ 9 ] used FeCl 3 to etch 304 stainless steel and found that the surface roughness and the nonuniformity of the flow path edge increased with the increase of etching time.…”
Section: Introductionmentioning
confidence: 99%
“…For this study we have kept following parameters as constant; developing time as 120 seconds, concentration as 400 grams per liter and etching time as 300 seconds PCM combines chemical etching with micro-photography and photosensitive etchant. Cakir [4]and Saraf et al [5]studied the effect of concentration, temperature, additives and etching time on responses like etch rate and surface finish for copper etching. Cakir [4] also studied the simultaneous regeneration of waste etchant.Atul R. Saraf and MudigondaSadaiahet al [6] studied Magnetic field-assisted photochemical machining (MFAPCM) of SS316L and found that the etch rate is higher at higher temperature due to the higher rate of collusion between the atoms.N.D.Misalet al [6]…”
Section: Introductionmentioning
confidence: 99%